2012
DOI: 10.2147/ijn.s34635
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing microparticle internalization by nonphagocytic cells through the use of noncovalently conjugated polyethyleneimine

Abstract: Development of micro-and nanotechnology for the study of living cells, especially in the field of drug delivery, has gained interest in recent years. Although several studies have reported successful results in the internalization of micro-and nanoparticles in phagocytic cells, when nonphagocytic cells are used, the low internalization efficiency represents a limitation that needs to be overcome. It has been reported that covalent surface modification of micro-and nanoparticles increases their internalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The experiments described here demonstrate the practical feasability of WGM microlaser-based cell tracking by revealing broad compatibility with cells of different type and origin. For Hela and astrocytes, uptake of small microspheres with sizes ranging from 1 to 3 μm was reported previously21233233. However, here we have shown that with proper surface functionalization these cells can readily internalize WGM resonators with volumes 300-fold larger than this, thus revealing a surprising ability of cells to internalize large polymer spheres.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The experiments described here demonstrate the practical feasability of WGM microlaser-based cell tracking by revealing broad compatibility with cells of different type and origin. For Hela and astrocytes, uptake of small microspheres with sizes ranging from 1 to 3 μm was reported previously21233233. However, here we have shown that with proper surface functionalization these cells can readily internalize WGM resonators with volumes 300-fold larger than this, thus revealing a surprising ability of cells to internalize large polymer spheres.…”
Section: Discussionsupporting
confidence: 76%
“…In the literature, different liposome coatings have been reported to assist with the uptake of much smaller polymer microspheres (about 2 μm in size) by non-phagocytic cells212324. Liposomes consist of a formulation of neutral and positively charged lipid molecules that can facilitate contact and fusion with negatively charged cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, gene carriers with diameters larger than 200 nm are readily scavenged nonspecifically by monocytes and the reticuloendothelial system 36. A positive surface charge of GPE, which comes from the protonated amino groups on PEI, may be an advantage for cellular uptake, due to the electrostatic interaction between the negatively charged cellular membrane and the positively charged complexes 37,38. As shown in Figure 4, at a w/w ratio of 1, the particle size of GPE/pDNA complexes was 108 nm and the zeta potential was −8.9 mV, indicating that the complexation between GPE and pDNA was incomplete.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, with the aim to obtain cationic particles, several approaches have been performed, including their coating with cationic lipids or polymers. Specifically, particle coating with Polyethyleneimine (PEI) has been of particular relevance212223 due to the widely known protonsponge effect, which involves the protonation of PEI amine groups that leads to endo/lysosomal pH buffering, membrane disruption, and ultimate liberation of the content to the cytosol24. Moreover, the proton sponge effect has been shown to be more efficiently achieved when a high molecular weight of PEI is used25.…”
mentioning
confidence: 99%